Posaconazole: Use in the Prophylaxis and Treatment of Fungal Infections - Clark, Nina M.; Grim, Shellee A.; Lynch, Joseph P., III (Seminars in Respiratory and Critical Care Medicine, 2015)
Posaconazole, a fluorinated triazole antifungal drug, is approved by the U.S. Food and Drug Administration (FDA) for (1) prophylaxis against Aspergillus and Candida infections in immunocompromised patients at high risk for these infections and (2) oropharyngeal candidiasis (OPC), including cases refractory to fluconazole and/or itraconazole. The European Medicines Agency (EMA) has approved posaconazole for (1) treatment of aspergillosis, fusariosis, chromoblastomycosis, and coccidioidomycosis in patients who are refractory to or intolerant of other azoles or amphotericin B; (2) first-line therapy for OPC for severe disease or in those unlikely to respond to topical therapy; and (3) prophylaxis of invasive fungal infections in high-risk hematologic patients and stem cell transplant recipients. In addition to approved indications, posaconazole has been used with success as salvage therapy for invasive mold infections and endemic mycoses in patients who are refractory to or intolerant of other antifungal agents, and as prophylaxis or salvage therapy in children, for whom indications are more limited owing to a paucity of data. Posaconazole has potent in vitro activity against a broad range of fungi and molds, including Aspergillus, Candida, Cryptococcus, filamentous fungi, and endemic mycoses including coccidioidomycosis, histoplasmosis, and blastomycosis. Importantly, posaconazole is much more active than other azoles against many Mucorales species and the combination of posaconazole with other antifungal agents may be synergistic. Hence, posaconazole is a potential candidate as a single or combination agent for difficult-to-treat fungal infections. Posaconazole has an excellent safety profile; to date, serious side effects are rare, even with prolonged use. However, newer posaconazole formulations achieve higher blood levels and it remains to be seen whether this may lead to an increase in the rate of adverse effects. Currently, posaconazole is used predominantly for prophylaxis and salvage therapy of fungal infections in adults. Indications for use as initial therapy of fungal infections and for broader use in children will depend on the accrual of additional clinical data.
Keywords: posaconazole; fungal infections; mold infections; azoles; mucormycosis; Aspergillus